Seismic-induced dynamic responses in a poro-elastic seabed: Solutions of different formulations. Issue 131 (April 2020) - Chen, Weiyun; Jeng, Dongsheng; Chen, Wei; Chen, Guoxing; Zhao, Hongyi
Abstract: The evaluation of dynamic response in a porous seabed has been studied since the 1980s. However, most previous analytical investigations focused on the loading from ocean-wave action. In this paper, an analytical method is presented to study the soil displacements, pore pressures and effective stresses in a nearly saturated porous seabed subjected to earthquake excitation. Based on Biot's theory and the concept of homogeneous pore fluid, a set of analytical solutions for various response are derived in terms of seawater depth, seabed parameters and seismic characteristics of bedrock. Numerical examples are given to demonstrate the significant influences of saturation degree, soil permeability and excitation frequency on the earthquake-induced soil displacement and pore pressure in a nearly saturated seabed. In addition, to investigate the effect of inertia force on the induced response in soils, two common-used formulations, i.e., fully dynamic (FD form) and partly dynamic (PD form), are considered, respectively. The regions of validity for these two formulations are identified and depicted to help engineers to select the appropriate solution for the seismic analysis in coastal engineering practice. Highlights: The dynamic response of nearly saturated porous seabed subjected to earthquake excitation is studied analytically. Various seismic responses of seabed are derived in terms of seawater, seabed and earthquake parameters. The effects of saturation degree, soil permeability and excitation frequency on the earthquake-induced response are presented. Domains of applicability for FD form and PD form are proposed to help coastal engineers to select appropriate solution.